PSYCHOEMOTIONAL CHARACTERISTICS OF PREGNANT WOMEN AS A RESULT OF THE ASSISTED REPRODUCTIVE TECHNOLOGIES APPLICATION - Kotenok , Antonina; Vygivska , Liliya; Maidannyk , Іgor; Оleshko , Viktor (The Ukrainian Scientific Medical Youth Journal, 2019)
The issue of preserving the reproductive health of the nation in Ukraine is very acute. The psycho-emotional state of a woman is of particular importance for the prolongation of pregnancy and the normal course of labor. Violation of adaptive mechanisms which are aimed at restructuring the functional systems of the body during pregnancy and on the eve of childbirth, as well as the state of chronic stress contribute to the increase in the of obstetric and perinatal complications frequency and have an adverse effect on the course of pregnancy. The aim of the reaserch was to study the dynamics of psycho-emotional state features in pregnant women after assisted reproductive technologies (ART) application in order to improve the tactics of antenatal surveillance. To achieve this goal, 299 pregnant women were comprehensively examined in the dynamics of prospective observation, which were distributed as follows – the main group included 249 women whose pregnancy occurred as a result of the ART application. The control group consisted of 50 pregnant women with spontaneous pregnancy and its physiological course, which were registered for pregnancy at 6-8 weeks. The women of main group whose pregnancy occurred as a result of ART application were divided into three groups, depending on the factor that caused infertility. The first group included 94 women with tubal-peritoneal factor of infertility, the second group was formed by 87 women with endocrine factor of infertility, the third group included 68 women whose infertility was caused by the male factor. Pregnant women of the study groups by age, marital and social status, place of residence were representative, which allowed further to judge the differences caused by etiological factors of infertility. In order to determine the psycho-emotional state of pregnant women in the study groups in the screening mode, a clinical interview was conducted by filling out questionnaires that contained the constituent questions of the STAI tests in the modification of Yu. L. Khanin and the "Pregnant Attitude Test" by the method of I. V. Dobryakov. The obtained test results indicate that the average score of reactive anxiety in pregnant women of the main group exceeded the same indicator of the control group and was: 49 - pregnant women with tubal-peritoneal type of infertility, 56 - pregnant women with endocrine type of infertility, 44 - pregnant women with male factor of infertility, 24 - control group. According to the results of testing, a significant difference was revealed in the indicators of personal anxiety. The values of indicators of personal anxiety were: 51 - pregnant women with tubal-peritoneal type of infertility, 54 - pregnant women with endocrine type of infertility, 31 -pregnant women with male factor of infertility, 31 - control group. Low level of personal anxiety was observed in 26 (27,6%) pregnant women of I group, 29 (33,3%) pregnant women of II group, which is significantly less in comparison with the indicator of pregnant women of the control group – 33 (66,0%) and III group - 33 (48,5%) (p < 0,05). Moderate type of personal anxiety was observed in 46 (48.9%) pregnant women of group and 40 (45.9%) pregnant women of II group compared to the indicator of the control group – 11 (22, 0%) (p < 0,05). Moderate type of personal anxiety was determined in 25 (36,7%) cases in pregnant women of III group and did not differ significantly from the indicators of I, II and control groups (p > 0,05). A high level of personal anxiety was observed in 22 (23,5%) pregnant women of group I, 18 (20,8%) pregnant women of group II, which is significantly higher in comparison with the indicator of pregnant women of the control group – 6 (12,0%) (p < 0,05). Thus, the study of the psycho-emotional state of pregnant women after the application of ART deviations in the level of personal and reactive anxiety and pathological types of gestational dominant, which are inherent in pregnant women of the main group. Taking into account the above, we consider it appropriate to involve a psychologist to work with the examined pregnant women in order to correct the identified abnormalities.